The Role of Counseling Teachers in Efforts to Improve Student Achievement During the Covid-19 Pandemic - Junaid, Uswatun Hasanah; Mahmudah, Fitri Nur (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
Since the Covid-19 pandemic was declared by the world health organization (WHO) as a global disease, all sectors of life have implemented health protocols, including the education sector. If the distance learning policy is carried out in the long term, it is feared that it will negatively impact. Impact on children, among others; students drop out, achievement decline, violence against vulnerable children occurs, student discipline decreases, and learning motivation decreases. The empowerment of school counselors is one of the solutions to various student problems during the pandemic. The research method used is qualitative, with data collection techniques using observation and interviews. The research procedure uses the Miles & Huberman model. Data analysis was carried out using Atlas.ti software version 8. The results of this study indicate that there are eight roles of school counselors in improving student learning achievement during the pandemic. The roles of school counselors include; acting as a consultant, maximizing online tutoring, communication, flexibility in receiving and providing guidance, creating comfort, solving student problems, developing achievement, motivating, and building creativity. This role is carried out as an effort by the School Counselor so that students can maintain learning achievement and remain productive during a pandemic.Keywords: pandemic; the role of school counselor; achievement; students Sejak pandemi Covid-19 dinyatakan oleh organisasi kesehatan dunia (WHO) sebagai penyakit global, semua sektor kehidupan menerapkan protokol kesehatan termasuk sektor pendidikan. Jika kebijakan pembelajaran jarak jauh dilakukan dalam jangka waktu yang panjang dikhawatirkan dapat berdampak negatif. Dampak pada anak antara lain; siswa putus sekolah, prestasi menurun, terjadi kekerasan terhadap anak rentan, kedisiplinan siswa menurun dan motivasi belajar juga menurun. Pemberdayaan Konselor Sekolah menjadi salah satau solusi pada berbagai permasalahan siswa di masa pandemi. Metode penelitian yang digunakan adalah kualitatif, dengan teknik pengumpulan data menggunakan observasi dan wawancara. Prosedur penelitian menggunakan model Miles & Huberman. Analisis data dilakukan dengan menggunakan software Atlas.ti versi 8. Hasil penelitian ini menunjukkan bahwa ada delapan peran konselor sekolah dalam meningkatkan prestasi belajar siswa selama masa pandemi. Peran konselor sekolah diantaranya; bertindak sebagai konsultan, memaksimalkan bimbingan online, komunikasi, keluwesan dalam menerima dan memberikan bimbingan, menciptakan kenyamanan, mengatasi masalah siswa, mengembangkan prestasi, memberi motivasi dan membangun kreativitas. Peran ini dilakukan sebagai upaya dari Konselor Sekolah agar siswa dapat mempertahankan prestasi belajar dan tetap produktif di tengah pandemi.Kata kunci: pandemi; peran konselor sekolah; prestasi; siswa